A Vectorial Current Density Visual Inspection Method for IGBT Modules - Wu, Yangjing; Li, Hangcheng; He, Yichen; Li, Jing; Su, Huiyi; Shi, Chengyu; Zhang, Wenwei; Zhang, Mingji (IEEE transactions on electron devices, 2024)
Insulated gate bipolar transistor (IGBT) modules are extensively used in power electronic devices, renewable energy systems, and electric vehicles as key components because of their superiorities of high input impedance, high-speed switching, and low saturation voltage; however, they are usually subject to fault hazards of short-circuit (SC), overvoltage, overcurrent and over temperature. Traditional current-voltage inspection methods are limited by their mono-function of indicating fault status, but are incapable of evaluating fault reasons, position, and level. Here, we developed a novel vectorial current density visual inspection method based on the measurement of the magnetic field gradient generated by a current-carrying IGBT module. Experiments are conducted by scanning the tri-axial fluxgate sensor over the IGBT module in the standard operation condition. Vectorial features of divergence and curl images of vectorial current density are first studied. Typical fault inspection images with obvious characteristic differences are demonstrated based on an experimentally calibrated finite element analysis (FEA) model. A current density resolution of 8.459 A/m2 is achieved at a probe-to-sample separation of 22 mm, over a maximum scanning area of 400× 400 mm. Such a method is verified to be capable of imaging spatial vectorial current density, which may offer a novel visualizing technique for in situ inspection for next-generation power semiconductor devices and enable the potential of online health prognostics of power systems.